2018
DOI: 10.1371/journal.pone.0202117
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior and locomotion of the invasive Argentine ant from winter aggregations

Abstract: The collective behavior of ant colonies, and locomotion of individuals within a colony, both respond to changing conditions. The invasive Argentine ant (Linepithema humile) thrives in Mediterranean climates with hot, dry summers and colder, wet winters. However, its foraging behavior and locomotion has rarely been studied in the winter. We examined how the foraging behavior of three distinct L. humile colonies was related to environmental conditions and the locomotion of workers during winter in northern Calif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…Laboratory observations showed that treated workers stay alive for approximately 2 h before becoming symptomatic and unable to walk. The walking speed of Argentine ant workers is approximately 2 cm per sec 34 , equivalent to 108 meters per hour. Given that treated workers stay alive for at least 2 hours, they could have easily dispersed throughout the plots.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory observations showed that treated workers stay alive for approximately 2 h before becoming symptomatic and unable to walk. The walking speed of Argentine ant workers is approximately 2 cm per sec 34 , equivalent to 108 meters per hour. Given that treated workers stay alive for at least 2 hours, they could have easily dispersed throughout the plots.…”
Section: Discussionmentioning
confidence: 99%
“…To account for DeepLabCut tracking errors, any ant movement exceeding two millimetres per frame was considered implausible and subsequently removed. This is due to biological constraints that limit ants’ movement to a maximum speed of around one millimetre per frame (Burford et al ., 2018). In this process, an average of 0.1% [0%, 0.8%, N = 526] of frames were eliminated from each video.…”
Section: Methodsmentioning
confidence: 99%
“…Aktivitas semut mencari makan selain dipengaruhi faktor internal seperti rasa lapar (Howard dan Tschinkel 1980) juga dipengaruhi faktor eksternal seperti suhu pada semut Solenopsis invicta (Porter dan Tschinkel 1987) dan kelembapan pada semut Linepithema humile (Burford et al 2018). Penelitian O. smaragdina di wilayah urban telah dilakukan oleh Rizali et al (2008) dan Rezki et al (under review), namun belum ada penelitian di Indonesia yang membandingkan antar pulau untuk pemilihaan makanan dan pengenalan anggota koloni.…”
Section: Pendahuluanunclassified
“…Suhu luar di lokasi sarang relatif tinggi (28-31°C) dengan kelembapan yang rendah (55-75%), karena sarang terletak pada lokasi urban yang memiliki sedikit pepohonan. O. smaragdina merupakan semut rangrang yang aktivitasnya berhubungan dengan suhu (Mishra dan Bhadani 2017) dan kelembapan (Burford et al 2018). Akan tetapi, perilaku makan O. smaragdina di dalam kultur toleran terhadap suhu dan kelembapan, serta jika populasinya kecil aktivitasnya dipengaruhi oleh angin di awal sore hari (Greenslade 1972).…”
Section: Hasilunclassified